Mulberry (Morus alba L.) as an Agroforestry Plant in Uttaranchal - Kant, Rama; Chakrabarty, S.; Dhyani, S. K.; Upadhayay, R. K. (Indian Forester, 2004)
Sericulture based agroforestry system has great potential to generate larger income in Uttarandlal with its hilly , valley and tarai conditions. It is a job oriented agrohased industry , partieularly for the below poverty lille farmers. Uttaranchal has a long tradition of agroforestry that is widely practiced in all ecological and geographical regions. Farmers and land owners in different parts of Uttaranchal integrate a variety of woody perennials with the Mulberry crop and livestock production systems depending upon the agro-climatic conditions and local requirements. In addition to sericulture , Mulberry has a wide and diverse potential to protect the environment in varying agro-climatic conditions. It is perennial , deep rooted , widely adaptable with fast growing and determinate type of plant growth. It produces high biomass and foliage with rich in protein. Though it is medium sized tree but for intensive cultivation it is maintained as bushes of different sizes depending on suitability of the situation. Mulberry can be grown as a tree as well as in combination with agricultural crops (intercrop) to increase per unit area production as sericulture is a subsidiary crop in sub-tropical area. Mulberry plant is capable of meeting the present challenges of shortage of fuel wood , fodder , timber , unemployment , cottage industry , environmental degradation , protection and improvement of wastelands etc.